ANALISIS PENERAPAN METODE ECONOMIC ORDER QUANTITY PADA PERSEDIAAN BAHAN BAKU : STUDI KASUS PT IMECO BATAM TUBULAR TAHUN 2014 - Salesti, Jayana (MEASUREMENT, 2014)
The purpose of this study was conducted to analyze the application of the method to the economic order quantity of raw material inventory at PT Imeco Batam Tubular, based on the data in 2014. The data used are secondary data, inventories of raw materials companies in 2014. This study uses descriptive qualitative analysis techniques . These results indicate that by using economic order quantity will greatly minimize inventory costs and may reduce the risk of excess or shortage of raw material inventory